Expectant Management Versus Drug Treatment with Oral Contraceptive Pills in the Elimination of Pregnancy Remnants Caused by Incomplete Spontaneous Abortion in the First Trimester of Pregnancy: A Randomized Clinical Trial - Rahimi, Maryam; Jamshidnezhad, Niousha; Jayervand, Fatemeh; Shahbazi, Amirhossein; Kazerooni, Mitra; Mirsharifi, Maryam; Mokhtari, Khatere; Ranjbar Sadaghiani, Marjan (Archives of Advances in Biosciences, 2024)
Introduction: Various medical, surgical, and recently expectant methods are being considered for the removal of the retained products of conception caused by incomplete abortion. We aimed to assess the effectiveness and safety of oral contraceptive pills (OCP) and expectant (waiting) methods in the successful removal of these remnants. Materials and Methods: In this clinical trial, 58 patients were randomly treated with medication with OCPs, and the equivalent group of 58 patients were treated expectantly. The patients underwent treatment and intervention for three weeks, and then both groups underwent transvaginal ultrasound one week after the intervention to check whether they had successfully expelled the retained products of conception. The statistical software SPSS version 23.0 was used for the statistical analysis (IBM, Armonk, New York). P values of ≤ 0.05 were considered statistically significant. Results: In terms of the success in removing the retained products from the abortion, this success in the two groups treated with OCP and expectant management were 84.5% and 86.2%, respectively, which did not show a difference between the two groups (p-value > 0.05). In terms of other outcomes after the intervention, including infection, bleeding, and abdominal pain, no significant difference was observed between the two groups (p-value > 0.05). There was no significant difference between the two groups in the duration of full recovery and return to daily activities (p-value > 0.05). Conclusion: In the comparison of two medicinal methods regarding the complete disposal of abortion remnants, there is no difference in the success rate of the methods as well as the resulting complications including infection, pain, or bleeding. Also, the time to return to work and daily activities was similar in both groups.